2015
DOI: 10.1007/s00408-015-9802-y
|View full text |Cite
|
Sign up to set email alerts
|

MR-proADM Predicts Exercise Capacity and Survival Superior to Other Biomarkers in PH

Abstract: Different biomarkers reflect distinctive disease aspects in PH. NT-proBNP best predicts hemodynamic impairment while MR-proADM strongly correlates with exercise capacity. Additionally, MR-proADM represents a promising new marker to evaluate prognosis in patients with PAH and CTEPH. Multi-marker strategies should further be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
2
18
1
Order By: Relevance
“…showed that plasma MR-proADM correlated to exercise capacity (6MWD and peak oxygen consumption) and was also related to one-year mortality, which remained valid when investigating each subgroup alone. 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that plasma MR-proADM correlated to exercise capacity (6MWD and peak oxygen consumption) and was also related to one-year mortality, which remained valid when investigating each subgroup alone. 19…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Notably, a previous study has shown that MR-proADM is correlated to exercise capacity and related to one-year mortality in PAH and chronic thromboembolic PH (CTEPH) patients. 19…”
Section: Introductionmentioning
confidence: 99%
“…According to the study results, MR-proADM was found as a good predictor of short-and long-term allcause mortality in CAP patients. A recently published prospective multicenter study demonstrated that MR-proANP and MR-proADM were associated with exercise variables and prognosis in pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) (15). MR-proADM is a good prognostic indicator of mortality, and it may have a contributory effect in the risk stratification of acute dyspnea patients.…”
Section: Discussionmentioning
confidence: 99%
“…Andreassen et al ( 25 ) confirmed that the elevated levels of NT-proBNP in PAH patients are associated with hemodynamics. Kolditz et al ( 26 ) suggested that different biomarkers respond to different aspects of the pathogenesis of PH and NT-proBNP was significantly correlated with hemodynamics. The present study indicated that milrinone significantly reduces NT-proBNP and hsCRP in patients with PH-LHD.…”
Section: Discussionmentioning
confidence: 99%